Systematic position of Neocrangon communis (Decapoda, Crangonidae) based on the features of larval morphology - Sedova, Nina; Grigoriev, Sergey (Zootaxa, 2014)
The present article deals with morphological comparison of four species of shrimp larvae, such as Neocrangon communis and Mesocrangon intermedia, Crangon dalli and C. septemspinosa, inhabiting the Okhotsk Sea and north-western part of the Pacific Ocean. Morphological comparison of I–V zoeal stages is discussed. The main morphological differences of the appropriate larval stages are detected. Most features of C. dalli and C. septemspinosa are similar and differ from M. intermedia and N. communis. It is shown that M. intermedia and N. communis more similar species by their origin than it is accepted to think. It is assumed that these two species should be included into one genus—Mesocrangon. The figures of I, III–V zoeal stages are presented.